2012
DOI: 10.1016/j.visres.2012.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Rigid facial motion influences featural, but not holistic, face processing

Abstract: We report three experiments in which we investigated the effect of rigid facial motion on face processing. Specifically, we used the face composite effect to examine whether rigid facial motion influences primarily featural or holistic processing of faces. In Experiments 1, 2, and 3, participants were first familiarized with dynamic displays in which a target face turned from one side to another; then at test, participants judged whether the top half of a composite face (the top half of the target face aligned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
62
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(72 citation statements)
references
References 49 publications
8
62
2
Order By: Relevance
“…While such data suggests facial motion is perceived configurally, others argue it utilises part--based processing and therefore by--pass the inversion effect (e.g., Knappmeyer, Thornton & Bülthoff, 2003;Xiao, Quinn, Ge & Lee, 2012). Due to such mixed findings, we aimed to investigate this further within the current study.…”
Section: Introductionmentioning
confidence: 93%
“…While such data suggests facial motion is perceived configurally, others argue it utilises part--based processing and therefore by--pass the inversion effect (e.g., Knappmeyer, Thornton & Bülthoff, 2003;Xiao, Quinn, Ge & Lee, 2012). Due to such mixed findings, we aimed to investigate this further within the current study.…”
Section: Introductionmentioning
confidence: 93%
“…Rigid facial motion (i.e., head rotation and nodding) has been shown to eliminate the composite face effect (Xiao et al, 2012), but non-rigid facial motion (e.g., smiling) often does not (Cook et al, 2015;Favelle et al, 2015;Steede & Hole, 2006;Xiao et al, 2013). Such discrepant results occur not only between studies of rigid and non-rigid facial motion but also between different studies investigating non-rigid facial motion.…”
Section: Effect Of Facial Motion On Holistic Processing: Empirical Inmentioning
confidence: 99%
“…It has been shown that rigid facial motion eliminates holistic processing (measured as the composite face effect, Xiao et al, 2012). However, none of the theories of holistic processing described above predicts that rigid facial motion should remove holistic processing completely.…”
Section: Effect Of Facial Motion On Holistic Processing: Empirical Inmentioning
confidence: 99%
See 2 more Smart Citations